Relationship between HbA1c Levels and Severity of Diabetic Retinopathy: Doi: 10.36351/pjo.v37i4.1210 - Jamshed, Saima; Hanif, Ayesha; Malik, Irfan Qayyum; Zahid, Nukhba; Imtiaz, Hafiza Sadia (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the relationship between HbA1c and severity of retinopathy in diabetic patients. Study Design: Cross sectional study. Place and Duration of Study: Eye department of DHQ-UTH Gujranwala, from July 2020 to Dec 2020. Methods: An observational cross-sectional study including 100 patients was conducted at eye department of DHQ-UTH Gujranwala from January 2018 to December 2018. After approval from institutional review board, written informed consent with demographic variables was collected from every patient. Patients of either gender between 40-80 years of age with both types I and type II diabetes were included in this study. Complete ophthalmic examination including Best Corrected Visual Acuity, slit lamp biomicroscopy, Goldmann Applanation tonometry and fundus examination carried out. Diabetic retinopathy was classified from grade 0 to grade 5. Results: Out of 100 patients, 46 (46%) were males and 54 (54%) were females. Mean age was 60 ± 2.4 years with a range of 40 – 80 years among males and 40 – 70 years among females. Forty patients presented with grade 1 diabetic retinopathy and 4% presented with grade 5. Thirty two patients had good glycemic control while 20% had glycemic control of grade III. Patients with grade 4 diabetic retinopathy had the worst glycemic control of HbA1c level of 11.5. Conclusion: This study concluded that patients with poor glycemic control had severe diabetic retinopathy as compared to the patients with good diabetic control. There is a direct relation between HbA1c level and severity of diabetic retinopathy. Key Words: HbA1C, Diabetic retinopathy, Non proliferative diabetic retinopathy, Proliferative diabetic retinopathy, Vitreous hemorrhage.